2019
DOI: 10.21511/slrtp.8(2).2018.01
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the human security in Ukraine in a regional perspective

Abstract: The article investigates the theoretical aspects, features and the main directions of development of human security concept. On the basis of systematization of scientific sources; and summarizing the experience of scientists, whose works are devoted to the problems of analysis and assessment the level of human security, the author improved the system of indicators that underlies the classification regions of Ukraine. According to the results of cluster analysis, the regions are grouped into six clusters. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The dynamics of the quantitative distribution of Ukrainian regions by the selected clusters were also analyzed. The study identified cores with a constant composition of regions and presented characteristics of each cluster [ 28 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The dynamics of the quantitative distribution of Ukrainian regions by the selected clusters were also analyzed. The study identified cores with a constant composition of regions and presented characteristics of each cluster [ 28 ].…”
Section: Literature Reviewmentioning
confidence: 99%